PENGARUH MODAL DAN OMSET TERHADAP PENDAPATAN BADAN USAHA MILIK (BUM) DESA DI KECAMATAN ADIPALA KABUPATEN CILACAP - Rahmat Alhakim (Jurnal Inovasi Daerah, 2022)
BUM Desa is trusted by the Government to be able to improve the rural economy. In 2021 Cilacap Regency has established 269 BUM Desa, consisting of 59 Basic Stage, 179 Growing, 27 Developing and 4 Advanced. In running a business, BUM Desa can partner with individuals or groups. So, to maintain the trust of partners, BUM Desa must be able to manage capital into income and increase business scale. This quantitative study uses multiple linear regression analysis method, with primary data in the form of capital, turnover and income of 16 BUM Desa in Adipala District from 2018 to 2020, aiming to find out how much influence capital and business turnover have on income in BUM Desa. Based on the results of the analysis, it was concluded that Capital and Turnover partially and simultaneously had a positive and significant effect on BUM Desa revenue. Because the BUM Desa capital is dominated by the capital participation of the village government, this study recommends that BUM Desa can develop a business scale based on local potential to attract the community's interest to partner.